Effect of Chavyadi Masthu and Selected Yoga Techniques in Obesity - Dhiya George; Jyothi. R; Nafeesath Beevi. A (International Journal of Ayurveda and Pharma Research, 2025)
Obesity is a complex multi-factorial disease and a major risk factor for many non-communicable diseases which invites several pathological complications. Obesity is defined as abnormal or excessive fat accumulation that may impair health. The prevalence of obesity is now rapidly increasing worldwide due to increased sedentary lifestyles, physical inactivity, and unhealthy diets. Eating more calories than one burn in daily activity on a long-term basis causes the extra calories to add up and cause obesity. By proper Ayurvedic management which includes lifestyle modification in the form of a healthy diet and regular exercises like Yoga, the burden of obesity can be reduced. In this study, an Ayurvedic dietary formulation, Chavyadi Masthu and practice of selected Yogasanas were taken as interventions. 31 obese participants between the age group of 25 and 50 were selected and administered Chavyadi Masthu preparation with regular practice of selected Yoga techniques for 3 months. BMI, waist circumference, hip circumference, waist hip ratio and skin-fold thickness were assessed on 0th, 31st, 61st, 91st days along with lipid profile and FBS on 0th and 91st day. Analysis of data revealed that the interventions were effective in reducing body mass index, waist-hip ratio, waist circumference, hip circumference, skin-fold thickness, total cholesterol, serum triglyceride, LDL and VLDL and FBS levels and improvement in HDL with a significant level p<0.05.